Design and deformation pattern simulation of deep excavation support structures - Li, Shijiang; Wang, Fengcun; Le, Yi; Que, Qiaoyun; Su, Yu; Lin, Huiting (Frontiers in Earth Science, 2024)
This study delves into the design and deformation patterns of support structures in urban deep excavation projects, aiming to optimize the design of these structures to ensure their safety and stability. Initially, experimental research on steel-cement soil composite beams reveals their bending resistance and ductility under various loading conditions, confirming the effectiveness of the Soil Mixing Wall (SMW) method in enhancing the stability of support structures. Subsequently, theoretical calculations using the method of elastic support points were con-ducted and validated through a deep excavation project in Xi'an, demonstrating that this method accurately calculates the trends of horizontal displacement in support structures. Additionally, FLAC3D numerical simulations are utilized to analyze the patterns of horizontal and vertical displacement during the excavation process. The simulation results generally align with the actual measured data, showing that the support structures optimized by the elastic support points method effectively control horizontal displacement (maximum displacement of 47.8 mm) and vertical displacement (maximum heave of 67.3 mm), validating the effectiveness of the numerical simulation methods. This research not only provides theoretical and practical guidance for deep excavation projects but also holds significant reference value for the design and construction of similar engineering projects.